The Practitioners View About the Influence of the Deregulation - Chong, Suit Fong (2010)
In the last 2 or 3 years (since Dec of 2007), as the financial crisis caused by mortgage loan and financial derivatives over-leveraging, credit default swaps and collateralized debt obligations stroke United States of America's economy down, it spread to every corner of the world within 6 months, till late of the year 2008, nearly all of the industrialized countries has been undergoing a recession. Government and central banks was obliged to implement as much stimulation plans to retrieve the financial market from the edge of collapse. The emerging market such as China, Vietnam Thailand and Malaysia which are exporting oriented economies also greatly affected in the recession due to their heavily rely on US market and other industrialized countries.